The Diagnosis of Epilepsies - Grünewald, R A (J R Coll Physicians Lond, 1996)
Vague labels such as 'epilepsy', 'grand mal' or 'seizures' are detrimental to patient care, and should be universally abandoned in favour of the syndromic diagnosis of epilepsies.